Strategi Peladang Berpindah di Routa Dalam Rangka Menguatkan Klaim Hak Atas Tanah Bekas Areal Perladangan Berpindah di Masa Lalu - Sarlan Adijaya (Emik, 2020)
Claims of rights to land formerly shifting cultivation areas in the past, as referred to by the terms orawu, anahoma, laliwata and osambu are now increasingly ineffective - one of which is because the former shifting cultivation area has been abandoned for a long time where the trees have grown as usual, until hardly leaving the slightest sign of former swidden cultivation areas. As a result, lands in the former shifting cultivation areas in the past are now being taken over and controlled by other parties. This research, which lasted for six months, was conducted in Routa District, Konawe Regency, Southeast Sulawesi Province, considering that in this area a new phenomenon has developed in which land formerly cultivated areas in the past was re-opened by their descendants of current shifting cultivators in order to strengthen land rights claims. There are …. informants participated in this study, including shifting cultivators and descendants of shifting cultivators, government officials, and local law enforcers. Data collection techniques were carried out through interviews and observations. The study shows that the current strategy of the descendants of shifting cultivators in Routa is to re-open their parents' former shifting cultivation areas - this strategy is increasingly emphasized through planting growing crops, creating boundaries and legalizing land rights with both SKT and SHM. These strategies have proven to be quite successful in overcoming the encroachment of former shifting cultivation areas as well as providing new economic bases for shifting cultivators in the form of land and gardens.